LIKUIDITAS, LEVERAGE, PROFITABILITAS PENGARUHNYATERHADAP NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA MELALUI KEBIJAKAN DEVIDEN - Ainun Jariah (Riset Akuntansi dan Keuangan Indonesia, 2016)
The company’s value can be found on the ability to pay dividends. The amount of dividends paid to shareholders depend on the dividend policy of each company. This study aims to determine how the effect of liquidity, leverage, profitability toward dividend policy and the value of manufacturing companies in Indonesia. The number of samples are 8 manufacturing company. Data were analyzed using path analysis model. The results showed that liquidity, leverage, profitability have significantly influence on the company’s value, through the variable dividend policy shows the effect of the narrowing means that the value of the company was affected by the dividend policy is not significant. Partially, not all variables have a significant effect, just variables liquidity and leverage have correlation coefficient (R) of 0.574 with a significance of 0.025 which means proven strong correlation with the criteria. While the value of the coefficient of determination (R square) is 32.9%, which variables liquidity, leverage, profitability have influence to company’s value. Keywords: Liquidity , Leverage , Profitability , Dividend Policy , Values of Firm.